Compressive sensing based channel estimation for NC-OFDM systems in cognitive radio context - Xue-yun HE; Rong-fang SONG; Ke-qin ZHOU (Tongxin xuebao)
A new channel estimation based on compressive sensing(CS)in non-contiguous orthogonal frequency division multiplexing(NC-OFDM)system was proposed.As for NC-OFDM systems in cognitive radio context,the infrastructure of CS-based channel estimation,the design of pilot patterns and the algorithm of channel estimation were explored.Especially,a criterion of optimizing pilot pattern in the CS-based channel estimation was proposed by minimizing the mutual coherence of the measurement matrix in CS theory.Simulations show that,under many patterns of deactivated subcarriers,CS-based channel estimation obtains much better performance than existing NC-OFDM channel estimation methods in terms of the mean square error of the channel estimate as well as the bit error rate of the system.